Frequency of Ventilator-associated Pneumonia With 3-day Versus 7-day Ventilator Circuit Changes - Ting-Chang Hsieh; Shao-Hsuan Hsia; Chang-Teng Wu; Tzou-Yien Lin; Chih-Ching Chang; Kin-Sun Wong (Elsevier, 2010)
Ventilator-associated pneumonia (VAP) is a common clinical problem. Previous studies involving adult patient cohorts have assessed various risk factors associated with VAP, including ventilator circuit changes. The objective of this study was to examine the incidence of and risk factors associated with VAP, particularly 3-day versus 7-day ventilator circuit changes, in a pediatric intensive care unit (PICU). Methods: This was a cohort observational study. Patients hospitalized in the PICU at Chang Gung Children's Hospital between November 2003 and September 2004 were enrolled. Investigators and critical-care specialists evaluated baseline characteristics, incidence of VAP, and related variables from PICU admission until discharge or death. Results: Of 397 patients initially enrolled, 96 (aged 11-60 months) were available for statistical analysis and were assigned into two groups according to timing of ventilator circuit change: 3-day (n = 46) and 7-day circuit change (n = 50). No statistically significant differences were observed for VAP incidence (13% vs. 16%, p = 0.68) or hospital mortality (22% vs. 36%, p = 0.14) for 3-day versus 7-day circuit change. Incidence of VAP per 1000 ventilation days was 10.75 and 8.41 for 3-day and 7-day circuit change, respectively. Univariate analysis indicated statistical significance for the duration of mechanical ventilation (10.17 ± 16.63 days vs. 18.20 ± 14.99 days, p< 0.001), length of stay in PICU (22.30 ± 20.48 days vs. 37.22 ± 36.79 days, p= 0.0069) and presence of enteral nutrition [7 (15.22%) vs. 23 (46.0%), p = 0.0012]. Conclusion: Weekly circuit change does not contribute to increased rates of VAP in pediatric patients. Long-term studies evaluating risk factors in larger pediatric patient populations are warranted for further conclusive recommendations.